THE INFLUENCE OF USE MATERIAL LEAFLET IN THE RESULTS OF STUDENTS’ LEARNING ACTIVITY IN THE MATTER OF SYSTEMS DIGESTION - Achmad Fauzi; Tri Jalmo; Pramudiyanti Pramudiyanti (Universitas Lampung, 2013)
The result of Interviews and observations at SMP Negeri 5 Natar to class VIII students’ learning result in the subject matter of biology digestive system is still low. So we need variety of teaching materials to improve student learning result, an alternative instructional materials to improve learning result is a leaflet. The purpose of this study to determine the effect of the use of instructional materials leaflet with learning model STAD (Student Teams Achievement Division) against the learning result of students in the subject matter of the digestive system. The research design was a pre-test post-test non-equivalent, with random sampling cluster sampling technique. Quantitative data obtained from the average pre-test and post-test data analysis using t-test at 95% confidence level. Qualitative data obtained activity data and the intersting of teaching by materials leaflet.The results showed that there is significant inrease of the students’ learning result in the class that uses the material of instructional leaflet with the average - the average value of N-gain of 46.67. Improved student learning result are also influenced by students' learning activities using cooperative learning model type STAD which increased on average 0.26. Thus the use of teaching materials leaflet with type STAD cooperative learning model significantly affect the improvement of learning result and activities by students on the subject matter of the digestive system